Beyond the door of no return : confronting hidden colonial histories through contemporary art - Francone, Marcello; Wendt, Selene (Italy; Skira Editore, 2021)
The artists featured in this book create compelling narratives that shed light on the entangled colonial histories that connect Europe, Africa, the Caribbean and the Americas. Collectively, these artists provide crucial insight into some of the lesser-known aspects of colonial history, such as Norwegian involvement in the transatlantic slave trade. They describe the lives of freedom fighters such as Venus Johannes, Mary Thomas, Olaudah Equiano and Anna Heegaard. By highlighting the stories of those who have been historically silenced, we encounter a more nuanced understanding of colonial history and the factors that have contributed to the continued effects of colonialism today, most evidently witnessed in the prevalence of institutional, systemic and everyday racism, poverty and forced migration. Artists include: John Akomfrah, La Vaughn Belle, Manthia Diawara, Jeannette Ehlers, Michelle Eistrup, Sasha Huber, Oceana James, Patricia Kaersenhout, Grada Kilomba, Suchitra Mattai and Alberta Whittle.
English
Keywords: Colonial histories; N4390-5098 Visual Arts- Exhibitions; Transatlantic slave trade; Africa